Lake Toba Local Potential Utilization as a Learning Resource for Biodiversity Topic - Novita Manalu; Suhartini (Jurnal Penelitian Pendidikan IPA, 2023)
Learning process based on local potential has not been widely used in education, even though it is known that integrating local potential in education will make it easier for students to master subject matter because certain objects or phenomena can be seen directly. This research aims to analyze the local potential of Lake Toba waters to be used as a learning resource, especially regarding biodiversity topic. The research was carried out using an exploratory method to analyze and select various data sources related to the potential of Lake Toba as a learning source with secondary data types. The data obtained is then compiled, analyzed and concluded to obtain research results. The research results show that Lake Toba as one of the local potentials in the North Sumatra region has met the criteria required as a learning resource including the clarity of potential, alignment with educational goals, precision in targeting, transparent exploration guidelines, and a clear definition of anticipated benefits. Thus, it can be concluded that the local potential of Lake Toba can be used as a learning resource on biodiversity material in class X SMA/MA.